Impaired Stimulated Pancreatic β-Cell Responsiveness is a Dominant Feature of Bisphenol A-Associated Metabolic Dysfunction in Type 2 Diabetes: A Cross-Sectional Analysis of Adjusted Associations in an Indonesian Cohort - Yulianto Kusnadi; Ardianto Ardianto; Ratna Maila Dewi Anggraini; Sudarto Sudarto; Imran Imran (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Exposure to the endocrine-disrupting chemical bisphenol A (BPA) is a suspected contributor to the type 2 diabetes mellitus (T2DM) pandemic. This study aimed to move beyond simple correlation and investigate the adjusted association between urinary BPA and the dual pathophysiological defects of T2DM—insulin resistance and pancreatic β-cell failure—with a novel emphasis on contrasting basal versus stimulated β-cell function in an understudied Indonesian cohort. Methods: In a cross-sectional study, 40 patients with T2DM were recruited from a tertiary hospital in Palembang, Indonesia. Urinary BPA was quantified by liquid chromatography–mass spectrometry (LCMS). Insulin resistance was assessed by the homeostasis model assessment of insulin resistance (HOMA-IR). β-cell function was evaluated using the C-peptide index (CPI) at fasting and 1-hour post-75g oral glucose tolerance test (OGTT). Multivariable linear regression models were constructed to determine the association between urinary BPA (log-transformed) and metabolic indices, adjusting for age, gender, and body mass index (BMI). Results: After adjusting for confounders, higher log-urinary BPA remained a significant independent predictor of higher log-HOMA-IR (β = 0.58, 95% CI: 0.31-0.85, p < 0.001). BPA was also independently associated with poorer β-cell function, showing a significant inverse association with the fasting CPI (β = -0.45, 95% CI: -0.73 to -0.17, p = 0.003). Critically, this association was markedly stronger and more profound with the 1-hour stimulated CPI (β = -0.79, 95% CI: -0.99 to -0.59, p < 0.001). The variance in stimulated CPI explained by the model (R2) was substantially higher than for other indices. Conclusion: Higher environmental BPA exposure is independently associated with both heightened insulin resistance and compromised β-cell function in T2DM. The distinctly stronger association with impaired stimulated β-cell secretion, even after adjusting for key confounders, identifies a critical mechanism by which BPA may accelerate functional β-cell exhaustion, the pivotal event in T2DM progression.